Complete and assembled genome sequence of an NDM-5- and CTX-M-15-producing Escherichia coli sequence type 617 isolated from wastewater in Switzerland. (December 2018) - Zurfluh, Katrin; Stevens, Marc J.A.; Stephan, Roger; Nüesch-Inderbinen, Magdalena
Abstract: Objectives: Carbapenem-resistant Escherichia coli have emerged worldwide and represent a major challenge to effective healthcare management. Here we report the genome sequence of an NDM-5- and CTX-M-15-producing E. coli belonging to sequence type 617 isolated from wastewater treatment plant effluent in Switzerland. Methods: Whole-genome sequencing of E. coli 657SK2 was performed using Pacific Biosciences (PacBio) single-molecule real-time (SMRT) technology RS2 reads (C4/P6 chemistry). De novo assembly was carried out using Canu 1.6, and sequences were annotated using the NCBI Prokaryotic Genome Annotation Pipeline (PGAP). Results: The genome of E. coli 657SK2 consists of a 4.9-Mbp chromosome containing bla CTX-M-15, genes associated with virulence [ fyuA, hlyE, the pyelonephritis-associated pili ( pap ) gene cluster and the yad gene cluster], the copper resistance gene pco, and genes associated with resistance to quaternary ammonium compound (QAC) disinfectants ( emrA, mdfA and sugE ). A 173.9-kb multidrug resistance IncFII-FIA-FIB plasmid was detected harbouring aadA2, aadA5, bla NDM-5, bla OXA-1, cat, drfA, drfA17, the mph(A) – mrx – mphR cluster, the tetA–tetC–tetR cluster, and the virulence genes iutA and ylpA . Conclusions: The genome sequence of E. coli 657SK2 provides information on resistance mechanisms and virulence characteristics of pathogenic E. coli harbouring bla NDM-5 and bla CTX-M-15 that are spreading into the environment via urban wastewater.